Narrativas de travestis em situação de rua: cultura, educação e sexualidade - Matos, Camila Saraiva de (2021)
The scope of this study is to understand, through narratives, the gender educational practices of homeless cross-dressers in the city of Fortaleza, Ceará. Therefore, a series of non-directive interviews were carried out, between August 2016 and June 2019. The narratives reveal the knowledge that was constructed, experienced, and shared daily by the interviewees. The research approached the focus of informal education, taking as its theoretical foundation the ideas presented by: Libâneo (1994) and Brandão (2007). To discuss other issues, such as gender and sexuality, we used the theoretical framework developed by Louro (2014), Butler (2019), Foucault (1997), Santos (2015), Andrade (2012), Kulick (2008), among others. Regarding the cultural and ethnographic aspects involving the research field, the studies of Malinowski (1984), Geertz (2011) and Oliveira (2000) were taken as a basis. The narratives were based on authors such as Ferraroti (2014), Xavier (2014) and Pollak (1989). In addition, it was essential to debate the survival strategies of cross-dressers on the street, the behavioral norms of homeless people and the subjective actions that involve a whole context of marginalization, uses and abuses of the body, and the production of femininity. Concerning body transformations, the irreparable damage caused by the use of industrial silicone was discussed: "the pain of beauty". Throughout the study, issues such as prostitution and transphobia were also discussed. In this regard, this thesis exposed the ways in which cross-dressers re-signify their intersubjective relationships, their educational and socio-cultural contexts. Among the conclusions was that the cross-dressers decide to live on the streets after breaking family bonds, because their families reject the fact that they are cross-dressers; while others reveal that they have suffered sexual abuse and violence at home. Regarding their relationship with school, many were unable to finish elementary school and considered this institution as an excluding environment and a replicator of the prevailing order, which means that instead of deconstructing gender stereotypes, the school actually reinforces heteronormative standards.